Effect of River Salinity on Crop Diversity: A Case Study of South West Coastal Region of Bangladesh - Gain, Animesh K.; Aryal, Kul P.; Sana, Pritish; Uddin, Md Nazim (Nepal Agriculture Research Journal, 2014)
Saline water intrusion is a major problem and conflicting issue in south-west coastal region of Bangladesh. The increased salinity has negative impact on agricultural diversity in this region. The present study provides an assessment of perception of local farmers about changes of agricultural diversity mainly diversity of vegetable species (both summer and winter) and standing plants with the changes of salinity level in the nearby river. This study was carried out in January to August 2005 through semi-structured questionnaire in selected villages of different salinity prone areas such as high saline zone and moderate saline zone, namely Paikgacha and Rampal, respectively. The study has revealed that in Paikgacha, the salinity varies approximately within the range from 20,000 to 45,000 micro-mhos and in Rampal it is from 10,000 to 30,000 micro-mhos. Due to increased salinity, the summer vegetable species in Paikgacha and Rampal have been reduced from 16 to 2 and 15 to 9 respectively during the period 1975-2005. For winter vegetable species, this figure wasreduced from 13 to 9 in Paikgacha but in Rampal this number remained unchanged. Standing plant species in Paikgacha and Rampal have been reduced from 31 to 14 and 35 to21 respectively during that period. Agricultural diversity is reducing in substantial rate both spatially and temporally. Nepal Agric. Res. J. Vol. 8, 2007, pp. 29-37 DOI: http://dx.doi.org/10.3126/narj.v8i0.11576